Answer:
<em>A</em>(-3, 6), <em>B</em>(-1, -2), <em>C</em>(-7, 1)
Step-by-step explanation:
To the pre-image after a 270°-counterclockwise rotation [90°-clockwise rotation], just reverse it by doing a 270°-clockwise rotation [90°-counterclockwise rotation]:
Extended Rotation Rules
- 270°-clockwise rotation [90°-counterclockwise rotation] >> (x, y) → (-y, x)
- 270°-counterclockwise rotation [90°-clockwise rotation] >> (x, y) → (y, -x)
- 180°-rotation >> (x, y) → (-x, -y)
So, perform your rotation:
270°-clockwise rotation [90°-counterclockwise rotation] → <em>C</em><em>'</em>[1, 7] was originally at <em>C</em>[-7, 1]
→ <em>B'</em>[-2, 1] was originally at <em>B</em>[-1, -2]
→ <em>A</em><em>'</em>[6, 3] was originally at <em>A</em>[-3, 6]
I am joyous to assist you anytime.
Answer:
32,27,42,47,52
Step-by-step explanation:
Answer:
divide the interest amount by the product of the principal and time
Step-by-step explanation:
The simple interest formula is I = prt where I is the interest, p is the principal, r is the rate and t is the time (in years). Rewriting this formula so that r is the subject we get r = I / pt. Therefore the answer is divide the interest amount by the product of the principal and time.
Answer:
21. x = 5, 23.
Step-by-step explanation:
Answer:
13
Step-by-step explanation:
because 3+9=12+1=13